Genera of orders Actiniaria and Corallimorpharia (Cnidaria, Anthozoa, Hexacorallia), and their type species* - Fautin, Daphne Gail; Zelenchuk, Taras; Raveendran, Dinesh (Zootaxa, 2007)
We determined the type species, if any, for the 425 genera of the order Actiniaria and for the 19 genera of order Corallimorpharia. In Actiniaria, 393 genera have a clear type species; 46 generic names are homonyms, 17 of which are senior, 26 of which are junior (six have been replaced), and three are both junior and senior. Of the 18 available genera of Corallimorpharia, there are no junior homonyms, and one senior homonym.